Tušpa : The Capital of Urartians - Genç, Bülent,; Konyar, Erkan, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Tušpa (Tushpa), the capital of the Urartians who established their state on the Eastern Anatolian High Plateau in the 9th century BC, provides invaluable material remains-monuments and inscriptions-that help us understand this ancient civilization. This book presents the results of new research conducted between 2010 and 2019, building on nearly 170 years of ongoing studies in this ancient city. Tushpa, the earliest example of a new settlement model developed by Assyria's perennial enemy, occupies a strategic position on the high plateau north of the Taurus Mountains. Through this book, you will gain insight into the settlement policies of the Urartians, who built their cities in plains surrounded by impassable mountains. These policies are reflected in their inscriptions, architectural styles, and the intricate weaving of stone walls.